Model characteristics of physical development and special physical preparedness of swimmers 12–15 years old - Политько, Елена (Slobozhanskyi Herald of Science and Sport, 2018)
Оlena Politko Purpose: to develop model characteristics of indicators of physical development and special physical preparedness of young athletes of 12–15 years. Material & Methods: analytical generalization of scientific literature data, pedagogical testing, anthropometry, spirometry, methods of mathematical statistics. Results: established criteria for young athletes of different ages on the basis of indicators of physical development and special physical preparedness for the purpose of increasing the effectiveness of the intermediate selection in the acquisition of training groups. Conclusions: the use of the proposed model characteristics of physical development and special physical fitness of young athletes at the stages of preliminary basic and specialized basic training makes it possible to determine their prospects for further sports development.